2008
DOI: 10.1002/hlca.200890224
|View full text |Cite
|
Sign up to set email alerts
|

Clintoniosides A – C, New Polyhydroxylated Spirostanol Glycosides from the Rhizomes of Clintonia udensis

Abstract: Phytochemical analyses were carried out on the rhizomes of Clintonia udensis (Liliaceae) with particular attention paid to the steroidal glycoside constituents, resulting in the isolation of three new polyhydroxylated spirostanol glycosides, named clintonioside A (1), B (2), and C (3). On the basis of their spectroscopic data, including 2D-NMR spectroscopy, in combination with acetylation and hydrolytic cleavage, the structures of 1 -3 were determined to be (1b,3b,23S,24S,25R)-1,23,24-Introduction. -Clintonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…[25][26][27] Further inspection of the 13 C-NMR data of the sugar moiety in comparison with those reported in the literature showed that xylose and rhamnose, were attached to the C-3′ and C-2′ positions of the inner glucose, respectively, which in turn was attached to the C-1 position of the aglycone as in compounds 1 and 2. 18) This was also supported by the results of acid hydrolysis and the downfield shifts observed for C-1 (δ 84.7), C-3′ (δ 88.5), and C-2′ (δ 76.0). Compound 3 was then elucidated as (…”
Section: )supporting
confidence: 59%
“…[25][26][27] Further inspection of the 13 C-NMR data of the sugar moiety in comparison with those reported in the literature showed that xylose and rhamnose, were attached to the C-3′ and C-2′ positions of the inner glucose, respectively, which in turn was attached to the C-1 position of the aglycone as in compounds 1 and 2. 18) This was also supported by the results of acid hydrolysis and the downfield shifts observed for C-1 (δ 84.7), C-3′ (δ 88.5), and C-2′ (δ 76.0). Compound 3 was then elucidated as (…”
Section: )supporting
confidence: 59%
“…In particular, the observed HMBC cross-peaks (H1α and C19; H19 and C1) indicated that the hydroxyl group was coupled with the C1 of spirostane aglycone, and the configuration was determined as β by the coupling constant (J = 11.6, 6.1, and 4.8 Hz) of H1α and good agreement with those of clintonioside A. 23) In the NOESY spectrum, H1α also correlated with H3α and H9α. The HMBC cross-peak between H1′ and C3 proved that the glucopyranose was coupled with C3 of spirostane aglycone.…”
Section: Resultsmentioning
confidence: 70%
“…The quaternary carbon atoms were identifi ed using the assigned protonated carbon resonances by means of a long-range proton-carbon correlation experiment (HMBC). By comparison with literature data (Mimaki and Watanabe, 2008;Takaashi et al, 1995) the aglycon was identifi ed as (1β,3β,23S,24S)-spirosta-5,25(27)-diene-1,3,21,23,24-pentol. The 1 H and 13 C NMR signals are listed in Table I.…”
Section: Resultsmentioning
confidence: 81%
“…Due to the characteristic downfi eld shifts of C-1 and C-24 that were observed at δ C 84.5 and 83.1 ppm, respectively, glycosidic linkages in these positions could be assumed. Furthermore, the downfi eld shift of C-21 (δ C 69.5 ppm) in comparison with δ C 62.2 ppm for non-substituted derivatives (Mimaki and Watanabe, 2008) suggested a third glycosidation in this position.…”
Section: Resultsmentioning
confidence: 93%